Analysis of the Physico-Mechanical Properties of the Fiber in the Sliver of the Spinning Chambers (Texas Journal of Engineering and Technology, 2022)
In this article, the physical and mechanical properties of fibers that have passed through the pneumomechanical spinning machine discretization process have been studied. The results are carried out on modern equipment, the obtained values are analyzed in the form of histograms and conclusions are given.